Building a parallel corpus for Chinese folk songs translation studies: a case study of Northern Shaanxi and Hua’er folk songs - Yan, Li; Abdul Halim, Hazlina; Mohd Jalis, Farhana Muslim (Academy Publication, 2024)
Folk songs, collaboratively created by the public and transmitted orally, have gained widespread popularity. The translation of folk songs primarily centers on lyrics translation, a subset of literary translation. Recent advancements in corpus technology have highlighted the significance of corpus-based research approaches for the analysis of literary translation. The corpus method, now employed as a hybrid research approach, enables the generation of quantitative data for descriptive translation studies. Scholars are increasingly using parallel corpora containing both the source text (ST) and the target text (TT) to explore translation universals across diverse texts. Despite the growing body of literature on the translation of Chinese folk songs, most studies have involved straightforward analyses of a limited number of translated texts without the utilization of quantitative approaches. This article aims to bridge this gap by presenting a prospective study on the creation of the Chinese-English Parallel Corpus of Northern Shaanxi and Hua’er Folk Songs (CEPCNSHFS). The study covers essential aspects such as sampling, corpus structure, corpora selection, and corpora processing. Moreover, to assess the practical utility of the CEPCNSHFS, a pilot study was conducted. The primary contributions of this article reside in the potential of the CEPCNSHFS to support diverse research topics, including the exploration of translation language characteristics, styles, and methods employed in translating Northern Shaanxi and Hua’er folk songs, both of which hold significant positions within Chinese folk song traditions.